Identification of DREB Family Genes in Banana and Their Function under Drought and Cold Stress - Yi Xu; Yanshu Zhang; Funing Ma; Jingxi Zhao; Huiting Yang; Shun Song; Shaoling Zhang (Plants, 2024)
Bananas are one of the most important cash crops in the tropics and subtropics. Drought and low-temperature stress affect the growth of banana. The DREB (dehydration responsive element binding protein) gene family, as one of the major transcription factor families, plays crucial roles in defense against abiotic stress. Currently, systematic analyses of the banana DREB (MaDREB) gene family have not yet been reported. In this study, 103 members of the MaDREB gene family were identified in the banana genome. In addition, transcriptomic analysis results revealed that MaDREBs responded to drought and cold stress. The expression of MaDREB14/22/51 was induced by drought and cold stress; these geneswere selected for further analysis. The qRT-PCR validation results confirmed the transcriptome results. Additionally, transgenic Arabidopsis plants overexpressing MaDREB14/22/51 exhibited enhanced resistance to drought and cold stress by reducing MDA content and increasing PRO and soluble sugar content. This study enhances our understanding of the function of the MaDREB gene family, provides new insights into their regulatory role under abiotic stress, and lays a good foundation for improving drought and cold stress-tolerant banana verities.